Comparative study of conventional dressing vs. topical heparin dressing in lower limb diabetic ulcers - Ashok, N. M.; C., Balamurugan (International Surgery Journal, 2022)
Background: Diabetic ulcers are a serious complication of diabetes that results in significant morbidity and mortality, especially lower limb diabetic ulcers are very difficult to treat due to the poor vascularity and brittle granulation tissue formed during the healing phase, so conventional dressings might not be that effective in treating the wound so this study aims to study the effectiveness of topical heparin over conventional dressings for lower limb diabetic foot ulcers Methods: This is a prospective study done on 100 patients who presented to the surgical outpatient at Trichy SRM medical college hospital and research centre during the period December 2020 to July 2022 and diagnosed to have diabetic foot. Results: On comparing the patients results of both groups with conventional and topical heparin dressings, the group with topical heparin dressing showed significant reduction in hospital stay and wound healed faster than the group with conventional dressing Conclusions: Topical heparin dressing showed significant better results by reduction of hospital stay and faster healing of diabetic foot ulcers than wound treated with conventional dressing.